The Effects of Exchange Rate, BI Rate, and Money Supply on Inflation in Indonesia - Dalimunthe, Laila Ramadani; Bintoro, Nugroho Suryo (Contemporary Studies in Economic, Finance and Banking, 2025)
This study aims to analyze the effect of exchange rates, Bank Indonesia interest rates (BI-RATE), and money supply on inflation in Indonesia during the period January 2018 to December 2023. Using the Error Correction Model (ECM) approach, this study also highlights the phenomenon of rapidly increasing economic digitalization, which affects the speed of money circulation and inflation fluctuations through changes in consumption patterns and electronic transactions. The findings show that these three variables and the phenomenon of digitalization have an important role in maintaining inflation stability amidst global economic dynamics. This study emphasizes the need for integrated policy management to control inflation and encourage national economic growth.